The relationship between pitching parameters and release points of different pitch types in major league baseball players - Hashimoto, Yasuhiro; Nagami, Tomoyuki; Yoshitake, Shinji; Nakata, Hiroki (Frontiers in Sports and Active Living, 2023)
Objectives The purpose of this study was to deepen our understanding of pitches and to obtain basic knowledge about pitches by comparing 4-seam and other pitches in Major League Baseball (MLB). Methods We analyzed big data for 1,820 professional baseball pitchers of MLB on release speed, spin rate, release point 3D coordinates (X, Y, and Z axes), amount of change for 4-seam, and seven changing ball types (sinker, slider, changeup, cutter, curve, split finger, and knuckle curve), using PITCHf/x and TrackMan. We also evaluated three relationships: (1) between the release points and the ball types of pitch; (2) between the amount of change in the ball and the release speed; and (3) between the release speed and the spin rate. Results The release speed was significantly slower in seven changing ball types than in the 4-seam (p < 0.01, respectively). The spin rate and the amount of change (ΔX and ΔZ) were significantly different between 4-seam and seven changing ball types (p < 0.01, respectively). Release point 3D coordinates (X, Y, and Z axes) were significantly different between 4-seam and slider, cutter, and curve (p < 0.01, respectively). Based on these findings, the eight pitch types were mainly divided into three groups: 4-seam, curve, and off-speed pitch types. Conclusion Seven changing ball types included specific characteristics for each parameter. The correspondence among the release speed, ΔX, and ΔZ at the 3D coordinates is an arch with 4-seam as the apex. Our results suggest an effective strategy for changing the release point and displacement of a ball's trajectory to improve the performance of baseball pitchers.